Double stigma: a cross-sectional study of Lassa patients with hearing loss in North Central Nigeria - Best, Kachollom C.; Ameh, Emmanuel; Weldon, Caroline; Shwe, David; Maigari, Ibrahim Mahmood; Turaki, Ishaku; Ma’an, Nuhu D.; Yilgwan, Christopher Sabo; Makishima, Tomoko; Weaver, Scott; Paessler, Slobodan; Shehu, Nathan Y. (Frontiers in Public Health, 2024)
Introduction Lassa fever is a zoonotic infectious disease endemic in West Africa with a high case-fatality rate and reported stigmatization of surviving patients. This study examines discrimination among survivors of Lassa fever (LF) complicated by hearing loss (HL). Methods This cross-sectional qualitative study used an in-depth interview guide to collect information from patients with HL about their experience of stigma. Interviews were conducted by a trained team of interviewers at the Jos University Teaching Hospital between January and April 2022 in Hausa language after informed consent was obtained. Recordings of the interviews were transcribed and translated from Hausa to English. Data analysis was conducted using NVivo software using a thematic framework approach. Results Most (73%) respondents were male (n = 11); 27% were female (n = 4). The median age was 35 years (interquartile range, 16.5). Some Lassa fever patients experienced stigma and discrimination (53%) including isolation and withdrawal of family and community support during and after illness. HL increased stigma, as some patients were labeled “deaf” by other community members, increasing perceived stigma and devaluation. HL affected the socio-economic wellbeing of some who could not communicate well with their families and customers and constrained social interactions, evoking pain and apathy. Some survivors of LF and victims of its sequelae of HL experienced double stigmatization. While they were ill with LF, a third of respondents reported avoidance and isolation by family and community members who withdrew care and support both to them and their close family members. These forms of stigmatization strained their relationships. Conclusion There is a need to address stigma in LF survivors who develop HL through concerted community-owned awareness to improve their quality of life along with a robust social support system to aid prevention.